Catalytic Cracking Of Palm Oil Into Liquid Fuels: Kinetic Study - Twaiq, Farouq; Mohamed, Abdul Rahman; Bhatia, Subhash (2004)
The kinetics of the catalytic cracking of palm oil into liquid hydrocarbons are investigated and the catalytic cracking of palm oil was performed in a fixed bed microreactor, operated in the temperature range of 673 – 723 K and palm oil feed weight hourly space velocity (WHSV) of 1 – 4 h-1.